Haemostasis and metastasis: anticoagulants therapeutic potential in ovarian cancer - A. V. Vorobev; V. O. Bitsadze; J. Kh. Khizroeva; A. G. Solopova; D. M. Mamchich; E. D. Mun; D. V. Blinov; J.-C. Gris; I. Elalamy; G. Gerotziafas; P. Van Dreden; A. D. Makatsariya (Акушерство, гинекология и репродукция, 2025)
Aim: to perform a comparative analysis of epithelial ovarian cancer (ОС) recurrence rate in patients with/without long-term anticoagulant therapy (АСТ) as a part of secondary prevention of thrombotic complications.Materials and Methods. A prospective interventional non-randomized comparative study was conducted with 126 stage III–IV epithelial ОС patients. Main group patients (n = 66) received long-term АСТ (60–72 months) for secondary prevention of venous thromboembolic complications, while comparison group patients (n = 60) received no АСТ. Both groups were comparable in patient age, disease stage and amount of anticoagulant treatment. There were used direct oral anticoagulants: dabigatran, rivaroxaban and apixaban. ОС recurrence and thrombotic complications rate were assessed.Results. OC recurrence rate was found to be 31.8 % (n = 21) in main group and 65 % (n = 39) in comparison group (p < 0.05). The incidence of thrombotic complications was comparable between groups: 18.2 % versus 16.7 % respectively. The data show a significant decline in OC recurrence risk upon long-term АСТ.Conclusion. Long-term АСТ in patients with epithelial OC to prevent recurrent thrombosis may exert additional antitumour effect. The observed decline in OC recurrence rate supports the hypothesis that the haemostatic system is involved in the mechanisms of tumour invasion and metastasis. Further randomized trials are needed to evaluate efficacy of anticoagulants as potential modifiers of malignant neoplasm progression.